Board social capital and excess CEO compensation - Sauerwald, S.; Lin, Z.; Peng, Mike (2013)
We suggest that the board's external and internal social capital are important concepts that may affect the board's ability to keep excess CEO pay under control. Further, we bridge the board social capital research with sociopolitical factors in order to provide a more holistic theoretical rationale for excess CEO compensation.